Pedagogical Reflections and Practices of Prospective Elementary Teachers Through Video-Based Lesson Analysis: An Initial Metacognitive Examination in Lesson Study - Nugraha, Trisna; Susanti, Evi (Journal of Learning Improvement and Lesson Study, 2024)
The importance of teachers' thinking and practices in designing 21st-century student-centered learning has garnered increasing attention. Teachers are expected to possess the ability to create innovative and responsive instructional designs that cater to students' needs. This skill development must begin during teacher training programs. This study aims to analyze the reflections of prospective elementary teachers on the development of their pedagogical competencies through video-based lesson analysis (VBLA) as an initial part of lesson study. Using a descriptive qualitative research approach, the study involved 159 pre-service elementary teachers. Data were collected through instructional video screenings, observation sheets, questionnaires, and group discussions. The findings reveal that 6% of the participants demonstrated in-depth analysis, while 52% provided general yet less detailed evaluations. A key weakness identified was the lack of variation in teaching methods, with suggested solutions such as the use of deeper questioning to stimulate student discussions. This study emphasizes the importance of strengthening prospective teachers' metacognitive skills, particularly in conducting critical and reflective analysis, identifying instructional weaknesses, and redesigning lessons based on critical reflection. The integration of VBLA in teacher education is crucial to ensuring that prospective teachers acquire the necessary skills to design effective, student-centered learning.